Memenin atipik medüller karsinomu ( 4 Olgu ) - (:unkn) unknown (My University, 1998)
Medüller özellikler gösteren infiltratif duktal karsinomlar için atipik medüller karsinom tanımı kullanılmaktadır. Bu tümörlerin davranışı medüller karsinomlardan ayrım gösterir. Burada atipik medüller karsinom tanısı almış 4 olgu sunularak, bu tümörlerin histopatolojik özelliklerinin gözden geçirilmesi amaçlanmıştır. Olgulara östrojen ve progestron immun dokukimyasal boyaması uygulanmıştır. Olgularda infiltratif duktal karsinom ve atipik medüller karsinom ayırıcı tanısı Ridolfi kriterlerine göre yapılmıştır. Atipik medüller kanser az görülmesi nedeniyle 4 olgu eşliğinde sunulmuştur.

The name, atypical medullary carcinomas is used for infiltrative ductal carcinoma which has medullary properties. The behaviour of these tumors is different from medullary carcinoma. In this study we represented four cases, which have diagnosed atypical medullary carcinomas and to review histopathological features of these tumors. We were stained by immunhistochemical estrogen and progestron. Differencial diagnosed of these cases as infiltarative ductal carcinoma or medullary carcinoma has made for Ridolfi criterias. We described pathological features as rare atypical medullary carcinomas with 4 cases.
Atypical medullary carcinoma of the breast ( 4 Cases )